Sources of phenotypic variation of wood density and relationships with mean growth in two eucalyptus species in Argentina - Alarcon, Pamela Cecilia (2021)
Aims of the study: To describe the radial patterns of wood density, and to identify their main sources of variation, and the potential tradeoffs with mean tree growth, in two Eucalyptus species. Area of study: Mesopotamian (Corrientes and Entre Ríos provinces) and Pampean region (Buenos Aires province) of Argentina. Materials and methods: Eucalyptus grandis and Eucalyptus viminalis, growing in genetic trials installed in two sites per species were studied. X-ray wood microdensity profiles were developed from core samples. Each profile was proportionally divided in 10 sections. Mean, maximum, minimum and the standard deviation of wood density, for each section were computed. Mean annual growth was used to study the relationships with wood microdensity variables. A linear mixed-effects model computed the significance of different sources of phenotypic variation. Pearson´s correlation computed the relationships between variables. Main results: The pattern of radial variation in E. grandis showed a decrease in wood density from pith to bark, mainly due to the decrease in minimum wood density, while in E. viminalis, wood density increased towards the outer wood. In both species, the standard deviation of the wood density increased along the radial profile from pith to bark. Significant variation in wood density was explained by site, provenance and clone/family effects. In E. grandis mean, maximum and minimum wood density were negatively correlated with mean growth, whereas in E. viminalis correlations were positive but close to zero. Research highlights: Both the pattern of radial variation of wood density and the relationship between wood density and mean growth were different in the studied Eucalyptus species, and they varied within species depending on the site they were growing and genetic provenance.